2007
DOI: 10.1111/j.1574-6941.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition over a dry winter in meso- and eutrophic Portuguese water bodies

Abstract: In order to investigate the bacterial diversity in a number of rivers, reservoirs and lakes in northern and central Portugal during the winter of 2004/5 (atypically dry), we applied molecular methodologies, namely denaturing gradient gel electrophoresis with primers targeting fractions of the bacterial 16S rRNA gene. Environmental parameters such as pH, conductivity, inorganic nutrients, total suspended solids and chlorophyll a were determined in order to characterize the trophic status of the studied water bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
8
35
2
Order By: Relevance
“…In our study, different phylotypes showed various responses to environmental characteristics such as nutrient concentrations (DIN and SRP), conductivity, discharge, and dissolved oxygen. These results are consistent with those of studies in eutrophic lakes (37,48) and of similar investigations in rivers on bacterial community composition (13,35,49), where the dominance of different genotypes largely related to changes in nutrient concentrations and dissolved oxygen has been noted.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, different phylotypes showed various responses to environmental characteristics such as nutrient concentrations (DIN and SRP), conductivity, discharge, and dissolved oxygen. These results are consistent with those of studies in eutrophic lakes (37,48) and of similar investigations in rivers on bacterial community composition (13,35,49), where the dominance of different genotypes largely related to changes in nutrient concentrations and dissolved oxygen has been noted.…”
Section: Discussionsupporting
confidence: 93%
“…However, certain limitations, such as comigration of different DNA fragments and the presence of different bands with the same sequence in a single lane, have been noted that can introduce bias into the analysis and, therefore, jeopardize the correct interpretation of the data (39). The present study found no evidence for comigration of different DNA fragments; instead, bands in the community patterns could be unambiguously assigned to a single phylotype, since comigrating bands had identical or almost identical sequences, as previously found in several DGGE/TGGE studies (15,(32)(33)(34)(35)(36)(37). Although we cannot completely exclude the possibility of identical sequences from different bands in the same lane, the small number of such cases suggests that this is not a major concern for our analysis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…1 , manuscript in press at Environmental Microbiology (141a) (includes GenBank accession numbers FJ827781 to FJ828505); 2 , GenBank accession numbers for the sequenced clones are HQ386253 to HQ386631; 3 , GenBank accession numbers for the sequenced clones are FJ916807 to FJ916903 and HQ530565 to HQ532908, except HQ530583, HQ531638, and HQ532521. (Based on data from references 2, 3,4,11,20,22,24,27,35,38,41,42,44,45,46,48,49,52,61,63,69,73,74,82,83,84,85,89,93,95,101,105,106,108,116,124,126,127,134,135,139,140,141,147,148,149,15...…”
Section: Creating a Modern View Of Freshwater Lake Bacteriamentioning
confidence: 99%
“…Many cyanobacterial strains are alkali tolerant and grow at pHs ranging from neutral to 10 to 11, so that cyanobacteria both generate and thrive in alkaline conditions. There have been numerous reports of habitats where photosynthetic rates are high (such as shallow lakes), pH values exceed pH 10, and cyanobacteria become the major phytoplankton species (7,27). Such populations of cyanobacteria are frequently associated with the production of a range of secondary metabolites, including nuisance and toxic compounds (5).…”
mentioning
confidence: 99%